Pendampingan dan Pelatihan Metode Stoisisme Untuk Menurunkan Stres Dalam Merawat Lansia Demensia - Yenny Sima; Nurul Aisyiyah Puspitarini; Rezqiqah Aulia Rahmat; Madepan Mulia; Wahidyanti Rahayu Hastutiningtyas; Arnes Yuli Vandika; M.Khalid Fredy Saputra (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The concept of Stoicism has a main principle, namely living in harmony with nature that prioritizes reason or rationality. Islam highly values ​​the role of reason such as the teachings of Stoicism. Reason in Islam plays a very important role in increasing a person's level of faith and is one of the steps to gain peace of mind. The purpose of this PkM is to achieve happiness, peace, freedom from destructive emotions and control over desires. The therapy that is usually given to reduce stress basically has the principle of relaxation. The Method of Implementing Stoicism Stop-Think and Assess-Respon with focus group discussions and counseling methods. The results show that training and implementing the Stoicism method using the Stop-Think and Assess-Respon technique has an influence on changes in attitudes and behavior towards stress assessment in caring for elderly dementia. The evaluation of the results showed that the client understood dementia and how to treat it, and the participants understood and were able to carry out the Stop-Think and Assess-Respon method in solving their psychological problems.